Pengaruh Customer Experience sebagai Variabel Mediasi antara Brand Trust dan Brand Engagement terhadap Purchase Intention di Sektor Industri FMCG: Studi pada Konsumen Unilever Gen Z - Abdullah Asy-Syakur Azka; Amie Kusumawardhani (Diponegoro Journal of Management, 2026)
The fast-moving consumer goods (FMCG) industry is one of the sectors with significant growth, particularly in the beauty and personal care category. However, despite the growth of the industry, PT Unilever has experienced a decline in sales and market share in the domestic market. This condition creates a paradox, as brand trust and brand engagement toward several Unilever brands remain relatively high but have not been effectively converted into purchase intention. Therefore, by using customer experience as mediating variable, this study aim to examine how brand trust and brand engagement affect purchase intention. This research on Gen Z at Semarang City use Quantitative approach and survey as data collection methods. Purposive sampling technique was used in the process of determining and taking samples with the number of respondents involved being 214 people. Data were collected through an online questionnaire and analyzed using Structural Equation Modelling (SEM) with the assistance of SPSS and AMOS. This study`s findings indicate that purchase intention is positively and significantly affected by brand trust and brand engagement. Furthermore, this study also demonstrated that the relationship between brand trust and brand engagement on purchase intention is able to get mediated by customer experience.